Given:
The system of equation:
-------- (1)
--------- (2)
To find the values of x and y.
We will use substitution method.
From (1) we get,
![y = -4-x](https://img.qammunity.org/2021/formulas/mathematics/high-school/qc5uzsbrl58fbht2sar7adsqrpqd3k9d1v.png)
We will put the value of y in (1) and we get,
![-x-4 = x^(2) -6x](https://img.qammunity.org/2021/formulas/mathematics/high-school/t3w1iwuk0xipn88klj73akhvmtexzm0ygu.png)
or,
![x^(2) -5x+4= 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/xcanjtc4qcb4er1wzcwfjzl37e4cu6z7fc.png)
Now we will apply middle term factor method.
![x^(2) -(4+1)x+4 = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/p96h3rgtvy2x309qj1j3zsv3bz9oymk268.png)
![x^(2) -4x-x +4 = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/vezumd6uvya9b8fasa5lby4s1hhcht7imo.png)
![x(x-4)-1(x-4) = 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/rag9spudr2l74j62gcq2oty9328loasi17.png)
![(x-4)(x-1)= 0](https://img.qammunity.org/2021/formulas/mathematics/high-school/mo5a1e2e9j0f8yctq93zz8u2lqs7jdem8s.png)
so, x = 4 and 1
Now,
Substitute x = 4 in (1) we get,
![y = -4-4 = -8](https://img.qammunity.org/2021/formulas/mathematics/high-school/a5n19ockxw5u7yaf313hd9f3wzmxlvmo9m.png)
And putting x = 1 in (1) we get,
![y = -4-1 = -5](https://img.qammunity.org/2021/formulas/mathematics/high-school/2txsw5e0pofsth6ggtt3fsoxe107qgl1q8.png)
Hence, the solution of the given system of equation is (4,-8) and (1,-5)
Thus, Option A is the correct answer.